2007
DOI: 10.1177/0145482x0710100703
|View full text |Cite
|
Sign up to set email alerts
|

The Legibility of Typefaces for Readers with Low Vision: A Research Review

Abstract: This article presents a systematic review of the research evidence on the effects of the characteristics of typefaces on the legibility of text for adult readers with low vision. The review revealed that research has not produced consistent findings and thus that there is a need to develop standards and guidelines that are informed by evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 21 publications
0
28
0
3
Order By: Relevance
“…Adams & Hoffman, 1994; Mitzner & Rogers, 2003; Russell-Minda, Jutai, & Strong, 2007). However, the intriguing promise of our results is that by fitting our data to separate psychometric functions for older and younger participants, and then looking at the differences in fitted parameters, we can determine the level of blur or noise required to mimic the experience of an older participant for a younger participant.…”
Section: Discussionmentioning
confidence: 99%
“…Adams & Hoffman, 1994; Mitzner & Rogers, 2003; Russell-Minda, Jutai, & Strong, 2007). However, the intriguing promise of our results is that by fitting our data to separate psychometric functions for older and younger participants, and then looking at the differences in fitted parameters, we can determine the level of blur or noise required to mimic the experience of an older participant for a younger participant.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to read information on a computer display or small screen is crucial to full participation in modern society, and as the population ages and the proportion with visual impairments grows in developed countries, concern about the accessibility of information aimed at the general public will rise. 1 In Taiwan, the Physically and Mentally Disabled Population Survey reported that between 2000 and 2008, the number of people with a visual impairment rose from approximately 38,747 to 55,569, and during the same period, the number of people with low vision increased by 43.4%. 2 According to demographics from the 2000 U.S. Census, an estimated 2.4 million Americans (1.98%) had low vision in that year, and it is predicted that the number will increase by 70% to 4.08 million by 2020.…”
Section: Introductionmentioning
confidence: 99%
“…For the many individuals with low vision, reading text on a screen when planning and performing everyday tasks could present a major challenge. 1 In general, text is set in small sizes, and those with low vision might be expected to benefit from larger letter sizes. 4 Establishing one design that is appropriate for the "regular adult" population is of most interest to industry and society; however, people with low vision have difficulty reading standard print even with appropriate magnification and illumination.…”
Section: Introductionmentioning
confidence: 99%
“…). Legibility is maximised through optimal size, spacing and hierarchy of scale graduations and numbering ; and use of a specialist typeface . Drug names and concentrations are emphasised and differentiated through the use of ‘Tall Man’ lettering and highlighting .…”
Section: Methodsmentioning
confidence: 99%